THE PLEASURE FACTOR IN THE ANTHROPIC ENVIRONMENT AND THE GEOGRAPHY OF BEAUTY - Manoiu, Valentina-Mariana; Costache, Romulus; Spiridon, Razvan-Madalin (European Scientific Journal, ESJ, 2015)
The paper represents a socio-geographic analysis of the products, objects and entities designed and manufactured for an anthropic environment use, looking to evaluate the different types of pleasure and the emotional feedback generated by these elements. The analysis of the four types of pleasure, as well as the innate preference for beauty, was conducted in the urban areas of Lisbon, based on the observations collected in April 2014, with no claims to have gathered all the relevant examples for this modelcity. The conclusion is that the design-approach based on pleasure in the anthropic environment can now be significantly and systematically applied to help create a better environment, in terms of human emotional responses to it.